Formulation of Red Spinach Leaves (Amaranthus tricolor L.) Ethanol Extract Gel Dosage Form on Anti-Aging Activity - Simarmata, Yettrie; Syamsul, Darwin; Ardiani, Rani; Naldi, Jefri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Skin is the outermost organ that functions to protect muscles, ligaments and internal organs that can cause premature aging. Aging can be characterized by dry, thin, inelastic skin, wrinkles, death of skin cells, uneven skin tone, hyperpigmentation and hypopigmentation. Thus we need a protection such as anti-aging cosmetics. Antioxidants are often added because they can reduce oxidative damage caused by increased Reactive Oxygen Species (ROS) due to ultraviolet light exposure. The research method used experimental laboratory. This sudy aims to determine ethanol extract of red spinach leaves that can be formulated in gel form as well as whether it can provide anti-aging effects on the skin. Organoleptic, homogeneity, viscosity, pH, and dispersion tests are all used to evaluate the form. Using a skin analyzer, the gel dosage form's efficacy is tested for irritation and anti-aging properties. The findings demonstrated that there were no coarse grains and that the ethanol extract of red spinach leaves at concentrations of 1%, 3%, and 5% did not alter color, odor, or shape. The form has a pH between 4.5 and 6.5, a viscosity between 2000 and 4000 mpa, and it did not irritate the skin. Water content and wrinkles showed a significant difference (p<.05) in the one-way ANOVA test findings, however pores, smoothness, and stains showed no significant difference p>.05. Formula that provides potential results for anti aging activity is a gel with an extract content of 5%.